A case of allergic fungal rhinosinusitis caused by Schizophyllum commune identified in both patient's nasal sputum and veranda's soil samples. Issue 5 (May 2021) - Ueyama, Masako; Mizuno, Kazue; Hirose, Dai; Kamei, Katsuhiko; Ohta, Ken
Abstract: This is a case report of allergic fungal rhinosinusitis caused by Schizophyllum commune ( S. commune ) identified in a patient's nasal mucus and environmental soil sample using (r)DNA sequencing. Although filamentous basidiomycetes, including S. commune, are known as environmental pathogens causing allergic respiratory diseases worldwide, many patients with infections caused by S. commune have not been correctly diagnosed. Repeated exposures to environmental floating fungi supposedly make an easy sensitization and colonization of fungi in the nasal passages, resulting in the onset of allergic fungal rhinosinusitis due to S. commune in our living environments. This report indicates the importance of reconsidering allergic respiratory diseases associated with our living environments.